EKSPLORASI IMPLEMENTASI KURIKULUM BERBASIS TEKNOLOGI DALAM PENDIDIKAN DI SEKOLAH - UMMU ISTIQOMAH; AULIA UROHMAH; NAZWA LAILATUL HUFAFERA; NURHAYATI (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of information and communication technology has significantly influenced various aspects of education, including curriculum development and implementation. The integration of technology into the curriculum has become an important strategy to improve the quality of learning and to develop students’ 21st-century skills such as digital literacy, critical thinking, creativity, and collaboration. This study aims to explore the implementation of technology-based curriculum in secondary education, particularly focusing on its concepts, forms of implementation, and the factors influencing its success. This research employs a library research method by examining relevant scientific literature, including academic journals, books, and research reports related to the integration of technology in educational curricula. Data collection was conducted through documentation studies of credible literature sources, while data analysis was carried out using content analysis techniques to identify major themes within the reviewed literature. The results show that the implementation of technology-based curriculum in secondary schools is carried out through the use of digital learning media, online learning platforms, and the integration of technology in learning strategies and assessments. The integration of technology has been shown to improve learning effectiveness, expand access to learning resources, and increase students’ motivation and participation in the learning process. However, several challenges remain, including limited technological infrastructure, insufficient digital literacy among some teachers, and the lack of continuous professional training. Therefore, strong educational policy support, improvement of teachers’ digital competencies, and adequate technological facilities are necessary to optimize the implementation of technology-based curriculum in secondary education.